Rancang Bangun Infrastruktur Sistem Informasi Manajemen Sekolah untuk Pesantren - Joy Gabriel (Annual Research Seminar (ARS), 2016)
This paper discussses about the architecture development for school management information system. This system is online based and applied for pesantren (Islam based Indonesian education institute). School management information system is the solution of pesantren’s problem there are inefficientcy of time for every task in pesantren administration process and no direct connection for any stakeholder in pesantren. The arcitecture consist of the vision of pesantren until change management system for pesantren to adopt new system.